Conversational pursuit of medication compliance in a Therapeutic Community for persons diagnosed with mental disorders - Mortari, Luigina; Pino, Marco (Informa Healthcare, 2014)
Purpose: In this article, we contribute to the debate on medication compliance by exploring the conversational "technologies" entailed in the process of promoting clients’ adherence to psychopharmacological prescriptions. Using a case study approach, we explore how medication-related problems are dealt with in conversational interaction between the staff members and the clients of a mental health Therapeutic Community (TC) in Italy. Method: Four meetings between two staff members (Barbara and Massimo) and the clients of the TC were audiorecorded. The data were transcribed and analyzed using the method of Conversation Analysis.